2016
DOI: 10.1586/14760584.2016.1158108
|View full text |Cite
|
Sign up to set email alerts
|

New developments in an old strategy: heterologous vector primes and envelope protein boosts in HIV vaccine design

Abstract: Prime/boost vaccination strategies for HIV/SIV vaccine development have been used since the early 1990s and have become an established method for eliciting cell and antibody mediated immunity. Here we focus on induction of protective antibodies, both broadly neutralizing and non-neutralizing, with the viral envelope being the key target antigen. Prime/boost approaches are complicated by the diversity of autologous and heterologous priming vectors, and by various forms of envelope booster immunogens, many still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 166 publications
1
8
0
Order By: Relevance
“…For instance, scarification has traditionally been used to percutaneously deliver attenuated poxviruses as a highly effective smallpox vaccine (25). Moreover, combining different vector systems in heterologous prime-boost regimens often results in more potent immune responses (26). This often includes the use of DNA plasmids as the priming agent because it has been shown that DNA vaccines are safe and induce potent CTL responses, whereas there is no vector immunity (27).…”
Section: Importancementioning
confidence: 99%
“…For instance, scarification has traditionally been used to percutaneously deliver attenuated poxviruses as a highly effective smallpox vaccine (25). Moreover, combining different vector systems in heterologous prime-boost regimens often results in more potent immune responses (26). This often includes the use of DNA plasmids as the priming agent because it has been shown that DNA vaccines are safe and induce potent CTL responses, whereas there is no vector immunity (27).…”
Section: Importancementioning
confidence: 99%
“…However, the prime-boost immunization strategy is still an alternative approach for finding a cure against this important pathogen. For many years, research was focused on the induction of humoral immunity as the main arm of the adaptive immune response for a successful vaccine, but cellular immune responses have emerged as a key arm against the infected cells and viral reservoirs (43).…”
Section: Some Lessons Learned From Complementary Prime-boost Immunizamentioning
confidence: 99%
“…The prime-boost strategy has recently gained popularity and is a commonly used approach. In this setting, the immune system is primed by one vaccine candidate and boosted with either the same (homologous) or a different (heterologous) vaccine candidate (23). To understand the impacts of different boosts on the same prime, we made use of the RV132 and RV135 vaccine trials (the latter was a precursor study to the RV144 trial), in which the same prime, ALVAC, was boosted with either bivalent gp120 (bi-gp120), oligomeric gp160 (o-gp160), or AIDSVAX (A244) (24,25).…”
Section: Resultsmentioning
confidence: 99%